INDICATIONS AND COMPLICATIONS OF TRACHEOSTOMY AT A TERTIARY CARE INSTITUTE: A PROSPECTIVE AND OBSERVATIONAL STUDY - Sharma, Nitin; Sharma, Pritosh (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The aim of the present study was to present an analysis of indications and complications of tracheostomy in tracheostomized patients. Methods: This was a single center, hospital-based prospective, non-randomized, and non-comparative study involving 60 tracheostomized patients carried out from February 2021 to March 2022 at Geetanjali Medical College and Hospital, Udaipur, India. Results: Out of 60 tracheostomies performed most common indications were Laryngo-tracheal trauma (26.7%), organophosphorus poisoning (25%), malignancy of Larynx (11.67%), post-intubation stenosis (6.7%), bilateral abductor paralysis (6.7%), head injury (6.7%), meningitis (5%), acute laryngo-traheo-bronchitis (3.33%), hypoxic-ischemic-encephalopathy (3.33%), cerebrovascular accidents (1.67%), faucial diptheria (1.67%), and GB syndrome (1.67%). Out of 60 tracheostomies performed, 18 complications were encountered. The most common complication was granulations of tracheostoma which occurred in 5 cases (8.3%), three cases of tube occlusion (5%), three cases had difficult decannulation (5%), three cases developed infection of stoma (5%), two cases developed surgical emphysema (3.3%), one case of tracheostomy scar hypertrophy (1.6%), and one case developed tracheal stenosis (1.6%). Conclusion: Tracheostomy is the procedure of choice especially in cases. Where it is needed to provide prolonged positive pressure ventilation and tracheobronchial toilet. Thorough anatomical knowledge of trachea and adjacent structures, skill of surgeon, sterile technique, meticulous surgery, use of high-volume low pressure cuffed Portex tracheostomy tubes, and good bedside tracheostomy care results in minimal complications. Complications of tracheostomy are largely preventable.